The rising prevalence of HIV-1 infection in patients attending an inner city accident and emergency department. Issue 6 (November 1996) - Poznansky, M C; Walters, J; Cruikshank, A; Pollock, R; Dendrowskyj, P; Lewis, K; Parry, J V; Fothergill, J; Weber, J
Abstract : The recently published findings of the unlinked anonymous HIV prevalence study in England and Wales showed unchanging HIV prevalence in groups such as homo/bisexual men, and declining rates in non-injecting heterosexual men attending genitourinary medicine clinics. However, this multicentre study did detect a significant rise in seroprevalence rates in pregnant women in England and Wales and sentinel groups within hospitals in London, warning that changing patterns of HIV infection might account for these variable results. In 1992-1993 a seroprevalence study of adult patients attending the accident and emergency department at St. Mary's Hospital in West Central London showed a rate of HIV-1 infection of 1 in 77. We have repeated the seroprevalence study over the same calendar months in 1994-1995 to gain further information about HIV positive patients attending the department and to see whether a change in the patterns of HIV infection in the population served by St Mary's Hospital had occurred.